Is Caffeine Intake Associated with Urinary Incontinence in Japanese Adults? - Hirayama, Fumi; Lee, Andy (The Korean Society for Preventive Medicine, 2012)
Objectives: To investigate whether caffeine intake is associated with urinary incontinence (UI) among Japanese adults. Methods: A total of 683 men and 298 women aged 40 to 75 years were recruited from the community in middle and southern Japan. A validated food frequency questionnaire was administered face-to-face to obtain information on dietary intake and habitual beverage consumption. Urinary incontinence status was ascertained using the International Consultation on Incontinence Questionnaire-Short Form. Results: Mean daily caffeine intake was found to be similar between incontinent subjects (men 120 mg, women 94 mg) and others without the condition (men 106 mg, women 103 mg), p=0.33 for men and p=0.44 for women. The slight increases in risk of UI at the highest level of caffeine intake were not significant after adjusting for confounding factors. The adjusted odds ratios (95% confidence interval) were 1.36 (0.65 to 2.88) and 1.12 (0.57 to 2.22) for men and women, respectively. Conclusions: No association was evident between caffeine intake and UI in middle-aged and older Japanese adults. Further studies are required to confirm the effect of caffeine in the prevention of UI.